Correlation of Breeding Values Among Test Day Record at First, Second, and Third Lactations on Milk Production of Dairy Cattle - Karnaen, Karnaen; Arifin, J (ANIMAL PRODUCTION, 2009)
The research was conducted at Balai Besar Pembibitan Ternak Unggul Sapi Perah (BBPTU-SP) Baturraden, Purwokerto, Central Java. The aims of this research were to study: (1) Breeding Value among test day record at first, second and third lactations on milk productions of dairy cattle, (2) Correlation of breeding values among test day record at first, second, and third lactations on milk production of dairy cattle. There were 4964 records of milk productions for 9 years since 1997 to 2006 dividing on Â 2299, 1668, and 997 records at first, second and third lactations, respectively. The observed individuals recorded from 45 bulls and 640 known cows. Fixed Effects were analyzed using General Linier Model. Variance components were predicted using Restricted Maximum Likelihood (REML). Breeding value was predicted with Best Linier Unbiased Prediction (BLUP). Heritability was 0.198 at first lactation, 0,270 at second lactation, 0.006 at third lactation, and 0,115 at 1st, 2nd, and 3rd lactations. Breeding Value (BV) between 2.57 and -1,68 at whole lactation. Bull has a highest breeding value on 58-18-N number of whole lactation. Three cows have highest breeding values on number of 914 - 98 (BV = 2,57), 817 - 97 (BV = 1,93), and 882 - 97 (BV = 1,67). Based on Spearman correlation, second lactation was appropriate for selection, because had the highest correlation with whole lactation at 0,67 for whole animal and 0,71 for bull. (Animal Production 11(2): 135-142 (2009)Â Key Words: dairy cattle, breeding value, milk production, test day, lactation